The GOES‐R Solar UltraViolet Imager - Jonathan M. Darnel; Daniel B. Seaton; Christian Bethge; Laurel Rachmeler; Alison Jarvis; Steven M. Hill; Courtney L. Peck; J. Marcus Hughes; Jason Shapiro; Allyssa Riley; Gopal Vasudevan; Lawrence Shing; et al. (Space Weather)
Abstract The four Solar Ultraviolet Imagers (SUVI) on board the Geostationary Operational Environmental Satellite (GOES)‐16 and GOES‐17 and the upcoming GOES‐T and GOES‐U weather satellites serve as National Oceanic and Atmospheric Administration's operational solar coronal imagers. These four identically designed solar Extreme UltraViolet instruments are similar in design and capability to the Solar Dynamics Observatory‐Atmospheric Imaging Assembly suite of solar telescopes, and are planned to operationally span two solar cycles or more, from 2017 through 2040. We present the concept of operations for the SUVI instruments, operational requirements, and constraints. The reader is also introduced to the instrument design, testing, and performance characteristics. Finally, the various data products are described along with their potential utility to the operational user or researcher.